Capable Fish or Deficient Ponds? A Meta-Analysis of Consequences, Mechanisms, and Moderators of Perceived Overqualification - Liao, Meishi; Zhang, Melody Jun; Carnevale, Joel B.; Huang, Chengquan; Wang, Lin (Journal of Management, 2025)
Perceived overqualification (POQ) has traditionally been seen as an undesirable employment situation associated with negative outcomes. However, recent research suggests that POQ may have positive implications for both employees and organizations. Despite the growing literature on this topic, scholars have offered numerous explanatory mechanisms for linking POQ with its work outcomes, and inconsistent findings have been reported, highlighting the need for a comprehensive understanding of why, where, and for whom POQ is beneficial or detrimental. In the present study, we developed an integrative theoretical framework that depicts the consequences, mechanisms, and moderators of POQ. We then conducted a meta-analytical review of the POQ literature, analyzing 704 effect sizes from 251 independent samples (N = 87,229). By organizing the dominant mechanisms in POQ research within a unified framework of work motivation, we elucidate the distinct pathways by which POQ induces differential work consequences. We further consider the role of key cultural, economic, sociodemographic, and methodological characteristics as boundary conditions. Overall, our findings provide support for our predictions and provide novel insights into the work-related consequences of POQ. Theoretical and practical implications of our findings are thoroughly discussed.